The establishment of the ukrainian system of state secret protection. 1991–1994 - Vorozhko, Valeriy (Ukrainian Scientific Journal of Information Security, 2021)
The article examines the formation of state bodies of Ukraine responsible for information security, creation of a system of protection of state secrets, government communications, technical protection of information with limited access in 1991-1994 based on legislative acts of Ukraine, works of Ukrainian researchers and archival documents of the Central State Archives of Ukraine. Particular attention is paid to the regulations of Ukraine on the protection of state secrets and the activities of the State Committee of Ukraine for State Secrets. The author analyzes: the current situation related to the secrets of the military industry and the military department, inherited from the former Soviet Union and the Agreement of post-Soviet countries on mutual protection of interstate secrets; systematized carriers of classified information in circulation or stored at the time in regime-secret bodies; the comparison of the Soviet and Ukrainian systems of protection of state secrets; the process of forming the first Ukrainian code of information containing state secrets. The researcher also conducts a comparative analysis of the functions of the State Secretariat of Ukraine and the Security Service of Ukraine and the relative US government agencies, such as the Office of Information Security (ISOO) and the Federal Bureau of Investigation (FBI). The paper considers the role of the Ukrainian institute of "state experts on secrets" and problematic issues of material incentives for citizens to work under regime restrictions. The author provides examples of relict remnants of Soviet censorship and the transformation of Ukrainian censorship bodies. The research methodology is based on the principles of objectivity, positivism, systematics, historicism, and the following historical methods: problem-chronological, historical-comparative, historical-legal.